Novel resistance to Cydia pomonella granulovirus (CpGV) in codling moth shows autosomal and dominant inheritance and confers cross-resistance to different CpGV genome groups. - Annette J Sauer; Eva Fritsch; Karin Undorf-Spahn; Petr Nguyen; Frantisek Marec; David G Heckel; Johannes A Jehle (PLoS ONE)
Commercial Cydia pomonella granulovirus (CpGV) products have been successfully applied to control codling moth (CM) in organic and integrated fruit production for more than 30 years. Since 2005, resistance against the widely used isolate CpGV-M has been reported from different countries in Europe. The inheritance of this so-called type I resistance is dominant and linked to the Z chromosome. Recently, a second form (type II) of CpGV resistance in CM was reported from a field population (NRW-WE) in Germany. Type II resistance confers reduced susceptibility not only to CpGV-M but to most known CpGV isolates and it does not follow the previously described Z-linked inheritance of type I resistance. To further analyze type II resistance, two CM strains, termed CpR5M and CpR5S, were generated from parental NRW-WE by repeated mass crosses and selection using the two isolates CpGV-M and CpGV-S, respectively. Both CpR5M and CpR5S were considered to be genetically homogeneous for the presence of the resistance allele(s). By crossing and backcrossing experiments with a susceptible CM strain, followed by resistance testing of the offspring, an autosomal dominant inheritance of resistance was elucidated. In addition, cross-resistance to CpGV-M and CpGV-S was detected in both strains, CpR5M and CpR5S. To test the hypothesis that the autosomal inheritance of type II resistance was caused by a large interchromosomal rearrangement involving the Z chromosome, making type I resistance appear to be autosomal in these strains; fluorescence in situ hybridization with bacterial artificial chromosome probes (BAC-FISH) was used to physically map the Z chromosomes of different CM strains. Conserved synteny of the Z-linked genes in CpR5M and other CM strains rejects this hypothesis and argues for a novel genetic and functional mode of resistance in CM populations with type II resistance.